Characterization and Control of Pore Structural Heterogeneity for Low-Thermal-Maturity Shale: A Case Study of the Shanxi Formation in the Northeast Zhoukou Depression, Southern North China Basin - Liu, Enran; Liu, Chenglin; Shi, Dishi; Zhu, Disi; Xu, Qiuchen; Wang, Yanhong (Frontiers in Earth Science, 2022)
The Shanxi Formation layers in the northeast of the Zhoukou Depression, Southern North China Basin, mainly consist of dark mudstone interbed with tight stone and widely developed coal seam, which is a promising target for unconventional oil and gas exploration. A series of geochemical and geological methods were used to analyze the characterization and controls of the pores structural heterogeneity in low-thermal-maturity shale. These methods include the Rock-Eval analysis, total organic carbon (TOC) analysis, scanning electron microscope observation with an energy-dispersive spectrometer (SEM-EDS), X-ray diffraction, and low-pressure N2 adsorption. Based on these measurements, the pore diameter, specific surface area (SSA), and fractal dimension (D) were calculated, and then, the pore structure heterogeneity was analyzed. The result shows the pores of Shanxi Formation shale are mainly interparticle pores with low porosity and low permeability, and the pore structure is highly complex. The average fractal dimension of the micropore and the macropore are both 2.77, but that of the mesopore is 2.65, indicating a less-complex mesopore structure than the micropore and macropore. The S2, S1, and TOC exhibit no clear correlation with SSA and fractal dimension of pores, which proved the little impact of organic matter on the heterogeneity of pore structure in the low-maturity shale of the research area. The illite has a strong effect on the pore structural heterogeneity of Shanxi Formation shale. The samples with high content of illite show higher SSA, better physical properties, and low fractal dimension, reflecting low pore structural heterogeneity. However, the quartz and clay minerals show a slight correlation with SSA and no obvious relationship with the fractal dimension, indicating a little effect of them on the pore structure heterogeneity. The pore structural heterogeneity decreases along with the increase in porosity, while the permeability influenced by a variety of reasons under the compaction shows a poor relationship with SSA and fractal dimension. On the whole, the pore structural heterogeneity decreases for low-thermal-maturity shale with high content of illite and high porosity, which should be considered to be the better unconventional oil and gas reservoir in the research area.